Founders at work: Stories of startups' early days - Livingston, Jessica (Apress, 2007)
Presents the profiles of the founders of thirty-two start-up technology companies, discussing how their ideas originated, the obstacles thay overcame to make their companies grow into successful ventures, and the influence that many of these companies have on the Internet culture.